Study on depression among elderly people in an urban slum of Raichur - Ganganapalli, Vandana; N., Sujatha; Kurre, Bhaskar (International Journal Of Community Medicine And Public Health, 2019)
Background: Globally, more than 300 million people of all ages suffer from depression. With an ageing population, depression among the elderly is likely to increase in the coming years, with higher prevalence among the elderly people than that in the general adult population. This study was intended to know the prevalence of depression and factors associated with depression among elderly people. Methods: A cross-sectional study was conducted in the urban field practice area of Navodaya Medical College, Raichur. A pre-designed and pre-tested questionnaire was used to interview the elderly person, after taking verbal consent. Depression was assessed using geriatric depression scale (short version). The study duration was from 1st September 2018 – 31st December, 2018 with 360 sample size. Results: Out of 360 elderly people, the prevalence of depression was found to be 31.4 %. The prevalence of depression was more in females 31.9% (63 out of 197). Significant association of depression was noted with age, socio-economic status, marital status, type of family, education and occupation with p<0.05. Conclusions: Around 1/3rd of the study participants were found to be suffering from depression. Depression was significantly associated with age, illiteracy, nuclear family, dependent on family members. Family support to the elderly population may prevent depression.